Pemanfaatan AccuWheater API dalam Pengembangan Sistem Informasi Geografis Curah Hujan - Made Tri Ganesha; Widhy Hayuhardika Nugraha Putra; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Agriculture is a very important sector to be considered and developed by all person. The Government through the Minister of Agriculture Regulation No. 79 of 2013 concerning Guidelines for Land Conformity in Food Crop Commodities is one form of effort to develop the agricultural sector. In this regulation, the suitability of land of each plant in terms of various physical properties of the environment, one of which is rainfall. This research aims to help realize sustainable food agriculture by developing a geographical rainfall information system utilizing the AccuWheater API. The AccuWheater API is a service that provides information about the weather that can be accessed using Application Programming Interface technology. The system development process is done by Agile Method which is implemented on the website platform. This system has been tested using validation testing, usability testing, compatibility testing, and responsive testing. The results of validation testing with the black-box testing method obtained 100% valid results for 4 functional needs. Then the results of usability testing obtained an average value of 78.5 which means that the system created has a high level of acceptance and is included in grade C. Then for compatibility testing results show that the system can run well in all browsers tested. Finally, for responsive testing, the results show that the system can adjust the display according to the size and orientation of the screen.